2006
DOI: 10.1152/ajprenal.00134.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal polyuria in monosymptomatic nocturnal enuresis refractory to desmopressin treatment

Abstract: The transition from day to night is associated with a pronounced decline in diuresis with reductions in the amount of excreted water, electrolytes, and other end products of our metabolism. Failure to do so leads to a large urine output at night, a condition known as nocturnal polyuria, encountered in a large proportion of children with nocturnal enuresis. The aim of this study was to clarify the mechanisms responsible for the nocturnal polyuria seen in enuretics with inadequate response to desmopressin (dDAVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 40 publications
5
52
3
1
Order By: Relevance
“…Nocturia and nocturnal polyuria are symptoms of a variety of pathological conditions, including DM (24), cardiovascular diseases (25), renal diseases (26,27), and enuresis (28). It seems that different pathological mechanisms are responsible for abnormal circadian rhythm in diuresis (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturia and nocturnal polyuria are symptoms of a variety of pathological conditions, including DM (24), cardiovascular diseases (25), renal diseases (26,27), and enuresis (28). It seems that different pathological mechanisms are responsible for abnormal circadian rhythm in diuresis (11).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that different pathological mechanisms are responsible for abnormal circadian rhythm in diuresis (11). In children with enuresis, lack of a nocturnal increase in arginine vasopressin (AVP) level, disorders in hormones regulating renal sodium (aldosterone and angiotensin II), and overproduction of prostaglandin E2 (PGE2) have been reported (28)(29)(30)(31). The overnight decrease in blood pressure leads to an increase in AVP (32).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive nocturnal urine production in some children is based on abnormal nocturnal plasma vasopressin release. 6,7 Other children may have an "overactive bladder;" however, these children typically have daytime symptoms including urgency, frequency and incontinence. Yeung performed ambulatory cystometries and found that bladder overactivity is an important cause of therapyresistant nocturnal enuresis.…”
Section: Why Does Nocturnal Enuresis Occur?mentioning
confidence: 99%
“…If an average NUO on wet nights exceeded 130% of the expected bladder capacity for age (EBCFA), the child was defined as having nocturnal polyuria. 13 MVV was estimated as the maximal voided volume observed (morning void included), and the children with MVV less than 70% of EBCFA were considered to have a small bladder. 14 Daytime urodynamic studies were performed in all patients using DUET Logic urodynamic unit (Medtronic Corporation, Denmark) according to the recommendations of ICCS.…”
Section: Methodsmentioning
confidence: 99%